The scope of autonomy Kant and the morality of freedom - Deligiorgi, Katerina, 1965- (Oxford : Oxford University Press, 2012)
Katerina Deligiorgi offers a contemporary defence of autonomy which is Kantian but engages closely with recent arguments about agency, morality, and practical reasoning.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Autonomy (Philosophy); Kant, Immanuel, -- 1724-1804.